Administration of Safety in the Steel Industry - Haberstroh, Chadwick J. (Management Science, 1961)
Research in a single steel company highlighted the existence of autonomous safety goals and the importance of innovative activity in their realization. A key communications function in the process of innovation is performed by means of an industry-wide organization of staff specialists. Some confirmation of the relevance and effectiveness of this system is given by an analysis of plant injury rates for the steel industry as a whole.